Colostrum supplementation with n-3 fatty acids and α-tocopherol alters plasma polyunsaturated fatty acid profile and decreases an indicator of oxidative stress in newborn calves - Opgenorth, Julie (J Dairy Sci, 2020)
Our objective was to characterize the effects of supplementing newborn calves with n-3 fatty acids (FA) and α-tocopherol on blood lipid profiles and oxidant status in early life. Sixteen calves received 0 or 60 mL of 1:1 fish and flaxseed oil with 200 mg of α-tocopherol in 2.8 L of colostrum within 6 h after birth. Colostrum was >22% on the Brix scale. Blood was sampled on d 1, 2, 4, 7, 14, and 21 after birth for assessment of plasma polyunsaturated FA, α-tocopherol, total serum protein, and oxidant status index, an indirect indicator of oxidative stress that examines the balance between the concentration of reactive oxygen and nitrogen species and antioxidant capacity in serum. Health was observed daily. Weight and hip height were recorded at birth, 3 wk, and 8 wk. Data were analyzed with a Mixed procedure of SAS 9.4 (SAS Institute Inc., Cary, NC). Treatment did not alter concentration of total protein in blood serum, prevalence of diarrhea or other signs of disease, or rate of growth. Feeding n-3 FA and α-tocopherol increased plasma concentrations of the n-3 FA, including α-linolenic, eicosapentaenoic, and docosahexaenoic acids, with a concomitant decrease in oxidant status index during the first week of life. Concentrations of α-tocopherol decreased with supplementation, but all calves maintained adequate concentrations. Oxidant status index of treated calves returned to the level of control calves by d 14. We conclude that a colostrum supplement of n-3 FA and α-tocopherol is safe to administer to newborn calves, reduces oxidant status in the first week of life, and may improve health and performance.